The photophysics of Ruddlesden-Popper perovskites : a tale of energy, charges, and spins - Righetto, Marcello (2021)
Quasi two-dimensional halide perovskites (also known as Ruddlesden-Popper or RPs) are the most recent and exciting evolution in the perovskite field. Possessing a unique combination of enhanced moisture and material stability, whilst retaining the excellent optoelectronic properties, RPs are poised to be a game changer in the perovskite field. Spurred by their recent achievements in solar cells, light-emitting diodes and spintronic devices, these materials have garnered a mounting interest. Herein, we critically review the photophysics of RPs and distil the science behind their structure-property relations. We first focus on their structure and morphology by highlighting the crucial role of large cations: dictating the RPs’ layered structure and the statistical distribution of thicknesses (i.e., n-phases). Next, we discuss how optoelectronic properties of RPs differ from conventional halide perovskites. Structural disorder, stronger excitonic and polaronic interaction shape the nature of photo-excitations and their fate. For example, faster recombinations and hindered transport are expected for charge carriers in thinner n-phases. However, the complex energetic landscape of RPs, which originates from the coexistence of different n-phases, allows for funnelling of energy and charges. Presently, the photophysics of RPs is still nascent, with many recent exciting discoveries from coherence effects in the above-mentioned funnelling cascade to spin effects. Giant Rashba spin-orbit coupling, also observed in RPs, dictates their spin dynamics and provides exciting spintronics opportunities. To leverage these propitious RPs, future research must entail a cross-disciplinary approach. While materials engineering will unlock new chiral RPs and Dion-Jacobson variants, novel characterization techniques such as in situ synchrotron-based X-ray diffraction, ultrafast electron microscopy, and multi-dimensional electronic spectroscopy etc. are essential in unravelling their secrets and unleashing their full potential.